Relationship between Tectonism and Composition and Pore Characteristics of Shale Reservoirs - Fuhua Shang; Yanming Zhu; Haitao Gao; Yang Wang; Ruiyin Liu (Geofluids)
Tectonism is one of the major controlling factors of shale gas accumulation and enrichment in China. To explore the relationship between tectonism and composition and pore characteristics of shale reservoirs, this research carried out mineralogy tests, organic geochemistry tests, field emission scanning electron microscopy (FE-SEM) experiments, and low-pressure gas adsorption (LPGA, N2 and CO2) experiments on the shale samples of various deformation intensities from Southwestern China. Based on the FE-SEM image analyses, it can be found that there are large differences in pore characteristics in shale samples with different deformation intensities. The samples with strong deformation have more organic pores, mainly related to the clay-organic aggregates and rigid grains. Tectonism can cause organic matter (OM) and clay minerals to be mixed or OM to fill in the clay layers, resulting in the retention of some organic pores. It is the presence of pressure shadows around the rigid grains that can resist tectonic extrusion and protect some organic pores. LPGA experiment results also show that micropore-specific surface areas and pore volumes of the samples with strong deformation are larger than those with weak deformation. The shale samples with strong deformation also have more microchannels and microfractures. Tectonism can also cause some micropores to become macropores; for example, tectonism can cause the rigid grains to slide and rotate, enlarging the dissolution pores at the edges of rigid grains. Shale samples with strong deformation have a smaller mesopore volume; but due to the presence of organic-clay aggregates, a larger mesopore-specific surface area embarks on these samples. According to fractal dimension calculations, it is found that in strong deformed shale, more multiple dimensions of the pore system tend to represent rougher pore surfaces and more irregular shapes. Besides, rougher pore surfaces are eager to provide more adsorption sites and enhance the adsorption capacity of the deformed shale. This study investigates the relationship between tectonism and composition and pore characteristics of shale reservoirs and may promote understanding of the accumulation of shale gas in highly deformed areas.